Ancestry-dependent genetic structure of the Xq28 risk haplotype in the Mexican population and its association with childhood-onset systemic lupus erythematosus - García-Ortiz, Humberto; Barajas-Olmos, Francisco; Flores-Huacuja, Marlen; Morales-Rivera, Monserrat I.; Martínez-Hernández, Angélica; Baca, Vicente; Contreras-Cubas, Cecilia; Orozco, Lorena (Frontiers in Medicine, 2023)
Objective Here we aimed to investigate the association of the Xq28 risk haplotype (H1) with susceptibility to childhood-onset systemic lupus erythematosus (SLE), and to compare its frequency and genetic structure in the Mexican population with those in other continental populations. Methods We genotyped 15 single-nucleotide variants (SNVs) that form the H1 haplotype, using TaqMan real-time PCR. The association analysis [case-control and transmission disequilibrium test (TDT)] included 376 cases and 400 adult controls, all of whom were mestizos (MEZ). To identify risk alleles in Mexican Indigenous individuals, SNVs were imputed from whole-exome sequencing data of 1,074 individuals. The allelic frequencies determined in MEZ and Indigenous individuals were compared with those of the continental populations from the 1,000 Genomes database phase 3. Linkage disequilibrium (LD) analysis of risk alleles was performed on all populations. Interleukin-1 receptor associated kinase 1 (IRAK1) and methyl CpG binding protein 2 (MECP2) mRNA levels were determined using real-time PCR. Results Case-control analysis revealed genetic association with childhood-onset SLE for all 15 SNVs (OR = 1.49–1.75; p = 0.0095 to 1.81 × 10–4) and for the Xq28 risk haplotype (OR = 1.97, p = 4 × 10–6). Comparing with individuals of European ancestry (0.14–0.16), the frequencies of the risk alleles were significantly higher in the MEZ individuals (0.55–0.68) and even higher in Indigenous individuals (0.57–0.83). LD analysis indicated a differential haplotype structure within the Indigenous groups, which was inherited to the MEZ population as a result of genetic admixture. Individuals homozygous for the Xq28 risk haplotype exhibited decreased levels of both MECP2A and B transcripts. Conclusion We found that the H1 risk haplotype differs in its conformation in the Mexican population. This difference could be attributed to positive selection within the Indigenous population, with its inheritance now having an autoimmune health impact in both the Mexican Indigenous and MEZ populations.